Evaluation of the Urotest AB antibacterial substance detection test. Issue 11 (November 1994) - Blondeau, J M; Yaschuk, Y; Galenzoski, D; Hrabok, D; Isaacson, M; Lee, L; Link, H; Walshaw, L
Abstract : The Urotest AB was used to detect antimicrobial substances in urine samples. Of 1022 urine specimens evaluated, Urotest AB detected inhibitors in 38.9%. Of 159 urine specimens from patients thought to be taking an antibiotic, inhibitors were detected in 80.5%. This test may help to explain culture negative urine samples from symptomatic patients, and could help elucidate treatment failures and the epidemiology of antibiotic resistance.